Exploring chlamydia positivity among females on college campuses, 2008–2010. Issue 6 (17th August 2016) - Habel, Melissa A.; Leichliter, Jami S.; Torrone, Elizabeth
ABSTRACT: Objective : Describe chlamydia positivity among young women tested at college health centers by student characteristics: age, race/ethnicity, and institution type.Participants : During 2008–2010, colleges participating in a national infertility prevention program provided chlamydia testing data from females aged 18–24.Methods : Chlamydia positivity (number of positive tests divided by the number tested) among females stratified by college type (4-year versus 2-year and minority serving institutes [MSIs]) was determined.Results : Chlamydia testing data were provided by 148 colleges: 37 (26%) MSIs and 21 (15%) 2-year colleges. Of the 118, 946 chlamydia tests, 6.5% were positive. Chlamydia positivity in females at 4-year colleges was 6.6% versus 5.3% at 2-year colleges ( p = .0001). Positivity at MSIs was almost double of that at non-MSIs, 10.0% versus 5.4% ( p = .0001).Conclusions : Chlamydia positivity may be higher among college females than previously thought. Higher positivity at MSIs suggests that targeted sexually transmitted infection prevention efforts may be useful for high-risk college populations.